Multiplexed electrochemical and SERS dual-mode detection of stroke biomarkers: rapid screening with high sensitivity. (1st August 2019) - Sun, Jingyi; Zhao, Yi; Hou, Yajun; Li, Hanxia; Yang, Mingfeng; Wang, Ying; Sun, Baoliang
Abstract : In this work, a real-time assay for a highly sensitive, label-free, multiplexed electrochemical and surface-enhanced Raman spectroscopic (SERS) detection of stroke biomarkers by neuron-specific enolase (NSE) and S100-β protein was developed using lateral flow devices. Abstract : In this work, a real-time assay for a highly sensitive, label-free, multiplexed electrochemical and surface-enhanced Raman spectroscopic (SERS) detection of stroke biomarkers by neuron-specific enolase (NSE) and S100-β protein was developed using lateral flow devices. We found two kinds of Raman dye (Nile blue A (NBA) and 4-mercaptobenzoic acid (4-MBA))-decorated Au@AgNPs, which show both strong SERS signals and electrochemical redox characteristic peaks. The lateral flow assays are performed by a two-biomarker method for the first time. A sandwich structure contains the Raman dye-labeled Au@AgNPs with the first antibody, the second antibody immobilized on the lateral flow assay biosensor, and the target antigens. Thus, in the presence of the target antigens, the Raman dye-labeled Au@AgNPs could be bonded to the modified lateral flow device surface by antibody–antigen–antibody interactions. As a result, a simultaneous immunoassay for NSE and S100-β based on multiple labels is developed using electrochemical and SERS immunoassays. The prepared immunoassay biosensor for the detection of NSE and S100-β shows high sensitivity, selectivity, low detection limit and long-term stability. Compared with different Raman signals and electrochemical characteristic peaks, this has the lowest detectable concentration for NSE and S100-β at a signal to noise ratio of 3. The proposed immunosensor can be applied to determine NSE and S100-β in human blood serum. In addition, the electrochemical and SERS immunosensor has potential applications in the diagnosis and treatment of strokes in the field of clinical research.